INFLAMMATORY MARKERS IN PATIENTS WITH OSTEOARTHRITIS AND ARTERIAL HYPERTENSION - E. U. Aleksenko (SPb RAACI, 2014)
Inflammatory markers and activity of lymphocyte-to-platelet adherence (LTA) have been studied in fifty-eight patients with osteoarthritis. Sixteen healthy individuals were included in the control group. Changed production of inflammatory cytokines, i.e. an increased concentration of pro-inflammatory cytokines (IL-1β, TNFα, IL-6), and increased activity of LTA have been observed in patients with osteoarthritis, as compared to the control group data. A correlation was found between the levels of inflammatory cytokine production, and activity of lymphocyte-to-platelet adherence.